Nilai Filosofis Dalam Kesenian Wayang Kulit Bagi Pembentukan Identitas Kultural Generasi Z Muslim Indonesia - Pradipa, Rafi; Syafitri, Lely Nur Hidayah; Nasruddin, Muhammad (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2024)
Wayang is an Indonesian traditional art form that is recognized by UNESCO. Indonesia Puppeteers' interpretations of characters have conveyed important messages. However, the globalisation era, which demands greater sophistication and modernity from technology, has an impact on the art of wayang, which is becoming less and less prevalent. The purpose of this study is to analyse the implications of philosophical values in puppetry as a strategy for forming the cultural identity of the Muslim z generation in Indonesia. Literature research concludes this is 1) That in puppet art, efforts to convey messages are carried out in an interesting, varied, innovative manner in the form of religious values, ethical values, moral values, sosial values, moral values, this is done to attract the younger generation to preserve puppet culture and love 2) The philosophical values of the wayang punakwan and pandawa puppet characters influence the z generation to be able to emulate, apply, imitate, understand the values of the puppet characters so as to create a form of creativity for the z Muslim generation in Indonesia to create love, empowerment to the art of puppetry.